2007
DOI: 10.2967/jnumed.107.044362
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET for Mediastinal Staging of Lung Cancer: Which SUV Threshold Makes Sense?

Abstract: 18 F-FDG PET is the most accurate noninvasive modality for staging mediastinal lymph nodes in lung cancer. Besides using visual image interpretation, some institutions use standardized uptake value (SUV) measurements in lymph nodes. Mostly, an SUV of 2.5 is used as the cutoff, but this choice was never deduced from respective studies. Receiver operating characteristic (ROC) analyses demonstrated that SUV thresholds of more than 4 resulted in the highest accuracy. But these high cutoffs imply high false-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(115 citation statements)
references
References 28 publications
2
111
0
Order By: Relevance
“…Furthermore, maximum SUV was as accurate as mean SUV in lymph node staging of lung cancer [25]. Optimal cutoff values of maximum SUV for lymph node metastasis in the present study were 4.4 for N1-N3 and 4.8 for N1-N2 lymph nodes, values that are similar to those of recently published results (SUVmax = 4.4-4.5) [26,27]. These values were not significantly changed in the ILD 1-3 and ILD 1-2 groups , and their sensitivity and specificity were moderate (sensitivity = 68.8%, specificity = 74.6-75.8%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, maximum SUV was as accurate as mean SUV in lymph node staging of lung cancer [25]. Optimal cutoff values of maximum SUV for lymph node metastasis in the present study were 4.4 for N1-N3 and 4.8 for N1-N2 lymph nodes, values that are similar to those of recently published results (SUVmax = 4.4-4.5) [26,27]. These values were not significantly changed in the ILD 1-3 and ILD 1-2 groups , and their sensitivity and specificity were moderate (sensitivity = 68.8%, specificity = 74.6-75.8%).…”
Section: Discussionsupporting
confidence: 90%
“…It is quite possible that patients with inflammatory lung disease had more false-positive lymph nodes with low to intermediate 18 F-FDG uptake and, thus, a higher-than-usual SUV was obtained for the highest accuracy. A visual interpretation is widely used for clinical PET interpretation of lymph node involvement [25][26][27][28][29][30][31]. Most of the previous comparative studies demonstrated that visual analysis of PET is superior or comparable to the semiquantitative method except for N3 lymph nodes [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake of the 18 F-FDG-avid LNs was also visually scored using three grades of intensity of mediastinal blood pool (0=similar with mediastinal blood pool, 1=faintly positive, 2=definitely positive). SUV threshold of 2.5 was used for differentiating between metastatic and benign LNs in lung cancer [13][14][15]. Highly attenuated nodes were defined as those that had HU max >120 [16] as one of the diagnostic criteria in determining benign LN in patients with non-smallcell lung cancer.…”
Section: Image Analysismentioning
confidence: 99%
“…The standardized uptake value (SUV) is a semi-quantitative analysis method for measuring FDG uptake and further evaluating the conditions of disease [3]. In general, both the tumor regions and the sFEPU regions have a higher SUV value (SUV≥2.5 [5]), and highlights in PET image. Therefore, in order to accurately detect the lymphoma, it's necessary to precisely distinguish them.…”
Section: Introductionmentioning
confidence: 99%